1996
DOI: 10.1038/380499a0
|View full text |Cite|
|
Sign up to set email alerts
|

A neural basis for lexical retrieval

Abstract: Two parallel studies using positron emission tomography, one conducted in neurological patients with brain lesions, the other in normal individuals, indicate that the normal process of retrieving words that denote concrete entities depends in part on multiple regions of the left cerebral hemisphere, located outside the classic language areas. Moreover, anatomically separable regions tends to process words for distinct kinds of items.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

97
849
3
25

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,361 publications
(990 citation statements)
references
References 42 publications
97
849
3
25
Order By: Relevance
“…The hypothesis that the anterior temporal lobes function as a cross-modal "hub" is supported by neuroanatomical observations (Gloor, 1997), functional neuroimaging data (H. Damasio et al, 1996;Gauthier, Anderson, Tarr, Skudlarski, & Gore, 1997;Gorno-Tempini, Wenman, Price, Rudge, & Cipolotti, 2001;Nakamura et al, 2001;Rogers et al, 2006;Scott, Leff, & Wise, 2003), and computational arguments (Rogers, Lambon Ralph, & Garrard, et al, 2004;, in addition to neuropsychological observations from SD (Adlam, Patterson, Rogers, Salmond, & Hodges, 2006;Bozeat et al, 2000;Bozeat, Lambon Ralph, Patterson, & Hodges, 2002;Patterson et al, 2006;Rogers, Lambon Ralph, Hodges, & Patterson, 2004). …”
Section: The Pdp Theorymentioning
confidence: 94%
“…The hypothesis that the anterior temporal lobes function as a cross-modal "hub" is supported by neuroanatomical observations (Gloor, 1997), functional neuroimaging data (H. Damasio et al, 1996;Gauthier, Anderson, Tarr, Skudlarski, & Gore, 1997;Gorno-Tempini, Wenman, Price, Rudge, & Cipolotti, 2001;Nakamura et al, 2001;Rogers et al, 2006;Scott, Leff, & Wise, 2003), and computational arguments (Rogers, Lambon Ralph, & Garrard, et al, 2004;, in addition to neuropsychological observations from SD (Adlam, Patterson, Rogers, Salmond, & Hodges, 2006;Bozeat et al, 2000;Bozeat, Lambon Ralph, Patterson, & Hodges, 2002;Patterson et al, 2006;Rogers, Lambon Ralph, Hodges, & Patterson, 2004). …”
Section: The Pdp Theorymentioning
confidence: 94%
“…They demonstrated that visual words produced large negative field potentials within the anterior portion of the left medial temporal lobe, in relation to orthographically illegal non-words. In a similar vein, neurological studies have shown that naming failures that are lexical in nature occur when a patient can describe and define an object, thus providing a semantic meaning of it, yet fail to produce its specific name (Carmazza, 1996;Damassio et al, 1996). Imaging studies as well as anatomical correlations have pointed to left temporal lobe involvement in lexical representation (Damassio et al, 1996).…”
Section: Attention and Semantic Processesmentioning
confidence: 98%
“…In a similar vein, neurological studies have shown that naming failures that are lexical in nature occur when a patient can describe and define an object, thus providing a semantic meaning of it, yet fail to produce its specific name (Carmazza, 1996;Damassio et al, 1996). Imaging studies as well as anatomical correlations have pointed to left temporal lobe involvement in lexical representation (Damassio et al, 1996). By contrast, structures of the left and right hemispheres support the distributed sets of conceptual features that provide meaning to words, and these features are thought to be collected in the left temporal lobe for further lexical processing and, ultimately, for speech production (Carmazza, 1996).…”
Section: Attention and Semantic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…These maps show little variation in response over the slice except for the contrast map obtained with the L-prior which has a cluster of large values in left anterior temporal cortex. Damage to this part of the brain is often associated with loss of personal knowledge, e.g., an inability to name famous faces (Damasio et al, 1996). The voxel in the center of this activated region (x = À42, y = À3, z = À18 mm) has an estimated effect size of 1.9%.…”
Section: Face-repetition Datamentioning
confidence: 99%